Meritocracy across Countries - Oriana Bandiera; Ananya Kotia; Ilse Lindenlaub; Christian Moser; Andrea Prat (Institute of Labor Economics (IZA), 2024)
Are labor markets in higher-income countries more meritocratic, in the sense that worker-job matching is based on skills rather than idiosyncratic attributes unrelated to productivity? If so, why? And what are the aggregate consequences? Using internationally comparable data on worker skills and job skill requirements of over 120,000 individuals across 28 countries, we document that workers' skills better match their jobs' skill requirements in higher-income countries. To quantify the role of worker-job matching in development accounting, we build an equilibrium matching model that allows for cross-country differences in three fundamentals: (i) the endowments of multidimensional worker skills and job skill requirements, which determine match feasibility; (ii) technology, which determines the returns to matching; and (iii) idiosyncratic matching frictions, which capture the role of nonproductive worker and job traits in the matching process. The estimated model delivers two key insights. First, improvements in worker-job matching due to reduced matching frictions account for only a small share of cross-country income differences. Second, however, improved worker-job matching is crucial for unlocking the gains from economic development generated by adopting frontier endowments and technology.
Keywords: C78; E24; J24; J31; O11; O12; 330; skills; sorting; matching; multidimensional heterogeneity; development accounting; wage inequality; gender; migration